2020
DOI: 10.1002/cssc.202000969
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Sustainable Preparation of Nonactivated Porous Carbon from Brewing Waste for High‐Performance Lithium–Sulfur Batteries

Abstract: The development of renewable energy sources requires the parallel development of sustainable energy storage systems because of its noncontinuous production. Even the most‐used battery on the planet, the lithium‐ion battery, is reaching its technological limit. In light of this, lithium–sulfur batteries have emerged as one of the most promising technologies to address this problem. The use of biomass to produce cathodes for these batteries addresses not only the aforementioned problem, but it also reduces the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…An activated carbon obtained from pig bones was a pioneer for this application. 27 Later, the carbons obtained from the biomass residues of vegetables and those from agrifood wastes (olive stone, 28 cherry pits, 29 rice husk, 30 coconut shell, 31 pistachio shell, 32 banana peel 33 or brewing waste, 34 among others) have become more relevant. The preparation methods are easier and faster than those of other forms of C. The carbonization and activation processes can be carried out in a single step, which along with the low-cost and ecofriendliness of the raw materials represent a viable alternative as a carbon matrix for sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…An activated carbon obtained from pig bones was a pioneer for this application. 27 Later, the carbons obtained from the biomass residues of vegetables and those from agrifood wastes (olive stone, 28 cherry pits, 29 rice husk, 30 coconut shell, 31 pistachio shell, 32 banana peel 33 or brewing waste, 34 among others) have become more relevant. The preparation methods are easier and faster than those of other forms of C. The carbonization and activation processes can be carried out in a single step, which along with the low-cost and ecofriendliness of the raw materials represent a viable alternative as a carbon matrix for sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 , 46 ] In this respect, outstanding studies have demonstrated that carbon‐based electrodes obtained from the recycle of bio‐waste products may represent a suitable alternative to enable sustainable and, at the same time, high‐performance energy storage devices. [ 47 , 48 , 49 ] Indeed, Li−S batteries relying on cathode materials derived from crab shells, [50] peanut shells, [51] olive stones, [52] rice husks, [53] cherry pits, [54] bamboo, [55] brewing waste, [56] and even jellyfish umbrellas have been proposed as possible alternatives. [57] Taking in mind these achievements, we have explored herein the concept of a full lithium‐ion‐sulfur battery based on sustainable materials according to the most recent worldwide plans of the green economy, in particular within the UE community.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22b,95,172,177,222 ] At the same time, in most of the cases, the LIB and Li–S still outperform the emerging SIB and KIB in terms of reversible capacity, rate capability, and capacitance retention (Figure 19b). [ 92,126,137,148 ] The emerging areas of research in biomass derived materials for lithium‐based batteries focus on improving the different aspects of the materials that can lead to enhanced specific capacity and rate capability. The process of carbonization and activation can be used to synthesize porous carbons but different functionalization strategies including doping with heteroatoms or metallic and nonmetallic species or hybridization are required to tune their electrochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 137 ] Copyrght 2022, Wiley‐VCH GmbH., SIB (S‐CMT derived from cotton roll). Reproduced with permission.…”
Section: Discussionmentioning
confidence: 99%